Faktor Yang Memengaruhi Perilaku Perawat Dalam Pemilahan Limbah Infeksius Dan Non Infeksius Di Ruang Rawat Inap Kelas 3 Rumah Sakit Umum Haji Medan - Megawati; M. Solikhul Huda; Asyiah Simanjorang (STIKes Payung Negeri Pekanbaru, 2020)
Hospital medical waste is infectious and dangerous which must be managed according to standard operating procedures so as not to cause health problems and environmental pollution. The nurses do the sorting of infectious and non-infectious medical waste that are not in accordance with the provisions, allegedly due to factors of understanding, attitude, limited facilities and information and there is no strict sanction application. The aim of the study was to analyze the factors that influence the nurse's behavior in sorting infectious and non- infectious waste.This study was an analytical survey research with a cross sectional study approach. The population was 59 class III inpatient nurses and all of them were used as research samples. The data collection technique used a questionnaire. The data were analyzed using univariate, bivariate and multivariate analysis using multiple logistic regression tests at the 95% significance level. The nurse's knowledge factor (0.019), attitude (0.035), facility availability (0.038), information availability (0.033), and policy (0.011) influenced the behavior in sorting infectious and non-infectious waste because it was smaller than 0.05, and education factor (0.943) and length of work (0.256) had no effect. The policy variable is dominant which affects the Exp (B) value of 19.040.